Building household economic resilience to secure a future for near shore fishers in the Philippines. (January 2019) - Lomboy, Cristopher G.; Belinario, Flora; Pomeroy, Robert; Pedrajas, Joey; Tirona, Raquel Sanchez; Box, Steve; Domondon, Paolo Roberto; Balbido-Ramirez, Kristine
Abstract: Resilience has become a key concept for addressing the vulnerability of small-scale fishing households in developing countries. While effort has gone into defining the concept of resilience in relation to fishing households; very little application of the concept exists in practice. An economic resiliency strategy was developed that builds resilience through improved household assets to reduce risks and vulnerabilities. A foundational conclusion of the strategy is the importance of linking household livelihood interventions to sustainable fishing behaviors. The conservation enterprise approach facilitated a mutually beneficial relationship between biodiversity conservation and livelihoods. Highlights: Resilience is a key concept for addressing the vulnerability of fishing households. Importance of linking household livelihood interventions to sustainable fishing behaviors. Conservation enterprises facilitates a relationship between conservation and livelihoods.